Peran Etika Administrasi Publik dalam Mencegah Maladministrasi di Indonesia - Winni Ahatri; Agung Ramadhan; Suci Rahmadini; Sindi Rahma Sari; Yulia Hanoselina; Rahmadhona Fitri Helmi (CV. ITTC INDONESIA, 2024)
Maladamization is one of the main problems that are often found in public services in Indonesia. The results of the study show that public administration ethics has an important role in preventing maladministration as well as being able to improve the image of public services, as well as being able to create a better organizational culture and government management. Public administration ethics has a very large contribution that can be used as one of the solutions to overcome more complex public service problems. This research uses a literature analysis method or literature study, namely by collecting various sources of literature ranging from books, to journals that are coherent with the research topic.